Transformation and Implementation of Sharia Principles In Management of Rural Agribusiness Business Development Programs - Rahmini Hadi (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2018)
One of the interesting things in the implementation of the Rural Agribusiness Development Program (PUAP) in Lemberang Village is the institutional transformation of the Agribusiness Microfinance Institution (LKMA) of the Ngudi Raharjo Farmer Group (Gapoktan) to become sharia-based. In connection with this, it is interesting to study: What is the transformation process of LKMA Desa Lemberang to become a sharia-based institution? How is the implementation of sharia principles in the management of the PUAP and LKMA Syariah program in Lemberang Village?; In accordance with the formulation of the problem, the purpose of this study is to describe the two research questions. This study uses qualitative research methods, with embedded case studies or embedded case studies. The results showed that the transformation process of LKMA Desa Lemberang became a sharia-based institution with the character background of the religious Lemberang Village community, as well as the practice of agricultural activities which essentially applied sharia values, namely the maro, mertelu, and mrapat principles. The relatively loose provision of PUAP financial management allows LKMA Desa Lemberang to change its financial management system from a conventional system to a sharia system. The implementation of sharia principles in the management of the PUAP and LKMA Syariah programs in Lemberang Village uses: (1) mudharabah contract, (2) musyarokah contract, (3) murobahah contract, and (4) Ba'il Istamal Ajil contract.